1998
DOI: 10.1021/la970807d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alkyl Chain Length on the Adsorption ofn-Alkyl Isocyanides (RN⋮C) on Gold Powder

Abstract: The chemisorption of the alkyl isocyanides n-butyl (C4H9NC), n-hexyl (C6H13NC), n-octyl (C8H17NC), n-dodecyl (C12H25NC), and n-octadecyl isocyanide (C18H37NC) on Au powder from 1,2-dichloroethane (DCE) was examined using both solution (FTIR) and surface (diffuse reflectance infrared fourier transform or DRIFT) spectroscopic techniques. For the isocyanides with fewer than 12 carbon units in their alkyl tails, equilibrium binding constants (K 1), surface coverages (n 1s and n a mol/gAu), and qualitative rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 39 publications
5
46
0
Order By: Relevance
“…This is caused by the donation of antibonding lone-pair electrons of the pendent isocyanide group to the Au nanoparticles. [43][44][45] Another advantage of organic isocyanide as a SERS probe is that the peak position of the NC stretching band is very sensitive to the applied potential under electrochemical conditions. This would suggest that the peak position of the NC stretching band could be used as an indicator of the surface potential of metal nanostructures.…”
Section: ·3 Surface Potential Of Metal Nanoparticlesmentioning
confidence: 99%
“…This is caused by the donation of antibonding lone-pair electrons of the pendent isocyanide group to the Au nanoparticles. [43][44][45] Another advantage of organic isocyanide as a SERS probe is that the peak position of the NC stretching band is very sensitive to the applied potential under electrochemical conditions. This would suggest that the peak position of the NC stretching band could be used as an indicator of the surface potential of metal nanostructures.…”
Section: ·3 Surface Potential Of Metal Nanoparticlesmentioning
confidence: 99%
“…This gold powder was re-used many times for both the adsorption and catalysis studies. Typically, the gold powder was cleaned before each use by treatment with ''piranha" solution (concentrated H 2 SO 4 /30% aqueous H 2 O 2 ) [20,21], which restored the powder to its original catalytic reactivity. If the gold powder were only washed with a solvent, e.g., MeOH, between catalytic runs, its activity would be slightly decreased ($10%).…”
Section: Introductionmentioning
confidence: 99%
“…The adsorptions of mono-, bi-and tridentate alkyl isocyanides on an Au powder surface have been investigated. 7,8 Lin and McCarley 9 reported that 1,6-diisocyanohexane could form a robust layer on Pt and Au surfaces. 4,4 0 -Biphenyl diisocyanide (BPDNC) was found to adsorb on Au with its one pendant NC group in reflection-absorption infrared spectroscopic, ellipsometric, and contact-angle measurement studies.…”
Section: Introductionmentioning
confidence: 99%